2022
DOI: 10.3390/su14010468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Characteristics of Native Wild Himalayan Fig (Ficus palmata Forsk.) from Pakistan as a Potential Species for Sustainable Fruit Production

Abstract: Wild Himalayan figs (Ficus palmata Forsk.), native to East Asia and the Himalayan region, are closely related to the well-known cultivated fig (Ficus carica L.), which is grown mainly in the Mediterranean region. The Pakistani state of Azad Jammu and Kashmir has a rich variety of figs. However, no comprehensive study has been carried out to utilise the diversity of these wild figs for possible use in sustainable fruit production. Therefore, the present study was designed to assess the variability of 35 wild fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…As well as leaf length and width at the range of (7.19 to 12.89 cm), and (6.47 to 10.12 cm) successively. The highest leaf petiole length and thickness was 38.28 mm and 2.99 mm, lowest value was 17.49 and 1.33 mm respectively(Khan et al, 2022), otherwise, these results nearly with our results since in our results, the wild g types were also existed.The wide range of variability found among the g accessions from the fruit traits. The results so con rm with the results found byAter et al, (2008) that the highest fruit weight value was 77.22g and lowest was 11.40g, as well as the ostiole diameter was ranged between (1.9 and 10 mm).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…As well as leaf length and width at the range of (7.19 to 12.89 cm), and (6.47 to 10.12 cm) successively. The highest leaf petiole length and thickness was 38.28 mm and 2.99 mm, lowest value was 17.49 and 1.33 mm respectively(Khan et al, 2022), otherwise, these results nearly with our results since in our results, the wild g types were also existed.The wide range of variability found among the g accessions from the fruit traits. The results so con rm with the results found byAter et al, (2008) that the highest fruit weight value was 77.22g and lowest was 11.40g, as well as the ostiole diameter was ranged between (1.9 and 10 mm).…”
supporting
confidence: 68%
“…The fruit length and width were changed from (21.34 to 48.83 mm) and (25.93 to 61.58 mm) respectively. In addition, fruit stalk length was varied from (2.95 to 16.3 mm) and diameter from (2.92 to 7.96mm) Khan et al, (2022),. showed the results less and slightly close to our results, that reported that the lowest and highest fruit weight among 35 wild g types was 2.65 and 9.66 g, and fruit length and width ranged from (11.25 to 29.85 mm) and (11.85 to 27.49 mm).…”
mentioning
confidence: 99%
“…are well adapted to local pedoclimatic conditions and, combined with easy propagation and production, can contribute to the local economy and have a significant impact on the socioeconomic and ecological balance. The results showed high variability in some of the studied traits of 35 accessions from different parts of northeast Pakistan, indicating their good potential for further improvement and use in sustainable agricultural production [12]. Results from the relatively limited number of sea buckthorn (Hippophae rhamnoides L. ssp.…”
mentioning
confidence: 93%
“…Several species of Ficus are utilized in traditional medicine for their anti-inflammatory, anti-tumor, and tonic properties. These species have a long history of being used as medicinal remedies (Kitajima et al, 1999;Ogunlaja et al, 2022;Khan et al, 2022). Ficus extracts have been reported to have potential benefits in treating a variety of diseases, including epilepsy, jaundice, influenza, whooping cough, tonsillitis, bronchitis, enteritis, bacillary dysentery, toothache, and bruises (Kitajima et al, 1999).…”
Section: Introductionmentioning
confidence: 99%